Bone morphogenetic protein 4 regulates immortalized chicken preadipocyte proliferation by promoting G1/S cell cycle progression - Hongyan Chen; Chang Liu; Chong Chen; Zhiyong Su; Jingting Shu; Ming Zhang; Hui Li; Bohan Cheng (FEBS Open Bio, 2019)
Bone morphogenetic protein 4 (BMP4) has been reported to regulate adipose development, but its role in preadipocyte proliferation has not been explored in vitro. Here, we investigated the effect of BMP4 on chicken preadipocyte proliferation using immortalized chicken preadipocytes (ICP1 cells) as a cell model. We report that BMP4 expression increases during preadipocyte proliferation. Overexpression and knockdown of BMP4 promotes and inhibits preadipocyte proliferation, respectively. In addition, overexpression of BMP4 decreased the number of preadipocytes at the G0/G1 phase of the cell cycle, and increased the proportion of cells at S phase. In contrast, knockdown of BMP4 increased the number of preadipocytes at the G0/G1 phase of the cell cycle, and decreased the proportion of cells at the S and G2 phases. Furthermore, overexpression of BMP4 promoted the expression of proliferating cell nuclear antigen (PCNA), Id2, cyclin E, and cyclin‐dependent kinase 2 (CDK2), while knockdown of BMP4 inhibited the expression of Id2, cyclin E, and CDK2. Finally, neither BMP4 overexpression nor BMP4 knockdown affected cell apoptosis. Taken together, our results suggest that BMP4 may promote proliferation of ICP1 cells by driving cell cycle transition from G1 to S phase.